THE ROLE AND TASKS OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN THE EDUCATIONAL PROCESS - Ne'matulla Abdukarimovich Gulbayev; Alina Viktorovna Martsinkovskaya (Web of Journals Publishing, 2024)
The article talks about the role and tasks of information and communication technologies in the educational process, and also summarizes the author's results of their use in this process.
Keywords: Information, education, process, technology, communication.